A concise and straightforward approach to total synthesis of (+)-Strictifolione and formal synthesis of Cryptofolione via a unified strategy. Issue 8 (18th April 2019) - Li, Xiaotong; Wang, Gaopeng; Zhang, Zhibin; Wu, Na; Yang, Qianqian; Huang, Shuangping; Wang, Xiaoji
Abstract: We describe a concise and straightforward approach to the total syntheses of (+)-Strictifolione and Cryptofolione in the longest linear sequences of four steps and six steps from 3-phenyl propanal and trans-cinnamaldehyde, respectively. The route utilized a titanium tetraisopropoxide/(R)-[1, 1'-binaphthalene]-2, 2'-diol catalyzed Mukaiyama aldol reaction, indium(0)-promoted Barbier reaction, and olefin cross-metathesis as the key reactions. Graphical Abstract: